2020
DOI: 10.1007/s12630-020-01610-x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Clinical Frailty Scale for perioperative frailty screening: a prospective observational study

Abstract: Purpose Perioperative frailty increases postoperative complications, mortality, and new functional dependence. Despite this, routine perioperative frailty screening is not widespread. We aimed to assess the accuracy of the Clinical Frailty Scale (CFS) as a screening tool prior to anesthesia, and to determine which health domains are affected by frailty. Methods In a prospective, single-centre observational study, we enrolled 218 patients aged C 65 yr undergoing elective and emergency surgery. The screening per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 38 publications
3
17
0
Order By: Relevance
“…24 Moreover, the EFS has shown good correlation with surgical outcomes including postoperative complications, 16,17 hospital LOS, 25 and postoperative mortality. 26 While the clinical frailty score has similar accuracy as EFS in identifying frail patients perioperatively, 27 it requires subjective clinical judgement so can be limited by inter-assessor variability. 28,29 It also does not include cognition and psychosocial assessment.…”
Section: Discussionmentioning
confidence: 99%
“…24 Moreover, the EFS has shown good correlation with surgical outcomes including postoperative complications, 16,17 hospital LOS, 25 and postoperative mortality. 26 While the clinical frailty score has similar accuracy as EFS in identifying frail patients perioperatively, 27 it requires subjective clinical judgement so can be limited by inter-assessor variability. 28,29 It also does not include cognition and psychosocial assessment.…”
Section: Discussionmentioning
confidence: 99%
“…This outcome is similar to a study that used the CFS compared with comprehensive geriatric assessment in the emergency department in the West of Ireland and found that the CFS has the following: sensitivity 51%, specificity 94%, PPV 93%, and NPV 57% when using the cut point of frailty at ≥ 5 [ 42 ]. A study that compared CFS screening and the Edmonton Frail Scale in the perioperative department of the Royal Melbourne Hospital revealed that the CFS has a sensitivity of 80.8% and specificity of 88.6% when using a CFS at ≥ 5 and that the area under the receiver operating characteristic curve was 0.91 (95% CI, 0.86 to 0.94) [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the newly translated Korean version of CFS recognized frail patients more effectively than other scales. Previous studies have suggested the CFS is a useful screening tool based on clinical judgement for measuring frailty [8,14]. the translated version was also administered successfully.…”
Section: Discussionmentioning
confidence: 97%
“…Frailty is either physical or psychological or a combination of both [2]. Physical frailty is characterized by diminished strength and endurance and reduced physiologic function [1] and associated with increased health-related outcomes in older populations, including hospitalization, nursing home admission, re-admission, and mortality [3][4][5][6][7][8][9][10]. Therefore, for physicians, frailty screening is useful for risk stratification, goal setting and advanced care planning, and frailty-targeted interventions [1,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%